EXPLORING THE ROLE OF INCOME ON LIFESTYLE PRACTICES AND HAPPINESS OUTCOMES: A MULTI-INCOME GROUP ANALYSIS - A, Jagadish; S, Umakanth (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study examines the relationship between income, lifestyle practices, and happiness across different income groups. Although income has traditionally been considered a key determinant of well-being, recent evidence suggests that the income–happiness relationship is not linear. Using a quantitative cross-sectional design, primary data were collected from 200 respondents belonging to low, middle, and high-income groups through a structured questionnaire. Regression analysis was employed to test the proposed hypotheses. The findings indicate that simplistic living and experiential consumption significantly enhance happiness, suggesting that non-materialistic and experience-oriented lifestyles improve subjective well-being beyond income levels. Additionally, sustainable consumption behaviours strongly predict simplistic living, highlighting the role of sustainability values in shaping lifestyles. Overall, income influences happiness indirectly through lifestyle pathways rather than income levels alone.